Length–weight and length–length relationships of some of the most abundant species in the fish catches of Lake Nokoué and Porto-Novo Lagoon (Benin, West Africa) - LEDEROUN, DJIMAN; LALEYE, PHILIPPE A. (My University, 2018)
The length–weight relationships (LWRs) and length–length relationships (LLRs) are presented for 18 commercial actinopterygian fish species found in Lake Nokoué and the Porto-Novo Lagoon. The fish were collected monthly from fishermen from June 2015 to May 2016. The sample size, length range, weight range, LWRs, LLRs, 95% confidence intervals of b, coefficient of correlation r2 and growth type are given for each species. Values of b were between 2.495 (Elops lacerta) and 3.235 (Polydactylus quadrifilis), and r2 values between 0.884 (Elops lacerta) and 0.999 (Acanthurus moroviae). The present study introduces what will serve as the first references regarding LWRs and LLRs for two species (Eleotris vittata and Lutjanus goreensis) in Lake Nokoué and the Porto-Novo Lagoon. These results will be very useful for future investigations pertaining to population assessment and sustainable conservation practices for the fish stocks in both study areas.
Keywords: Actinopterygii; Benin; ichthyofauna; length–length; length–weight